The impact of westerly wind bursts on the diversity and predictability of El Niño events: An ocean energetics perspective. Issue 13 (1st July 2014) - Hu, Shineng; Fedorov, Alexey V.; Lengaigne, Matthieu; Guilyardi, Eric
Abstract In this study, we apply ocean energetics as a diagnostic tool to investigate the impact of westerly wind bursts (WWBs) on the evolution, diversity, and predictability of El Niño events. Following Fedorov et al. (2014), we add an observed WWB to simulations within a comprehensive coupled model and explore changes in the available potential energy (APE) of the tropical Pacific basin. We find that WWB impacts strongly depend on the ocean initial state and can range from a Central Pacific (CP) to Eastern Pacific (EP) warming, which is closely reflected by the ocean energetics. Consequently, the APE can be used to quantify the diversity of El Niño events within this continuum—higher negative APE values typically correspond to EP events, lower values to CP events. We also find that a superimposed WWB enhances El Niño predictability even before the spring predictability barrier, if one uses the APE as a predictor.